2005
DOI: 10.1589/jpts.17.1
|View full text |Cite
|
Sign up to set email alerts
|

The Boundary of the Vastus Medialis Oblique and the Vastus Medialis Longus

Abstract: Abstract. There are no well-defined or documented boundaries for either the vastus medialis oblique or for the vastus medialis longus. The purpose of this study was to examine anatomically the boundaries of the vastus medialis longus and the vastus medialis oblique. In an embalmed adult cadaver, two vastus medialis muscles were examined by direct visual observation. Our observations indicate that the boundary of the vastus medialis oblique and the vastus medialis longus appears to be the line from the adductor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 5 publications
1
12
1
Order By: Relevance
“…1 b, e, f). This pattern has also been reported in other studies 2,12,14) . Other authors, however, found no specific pattern of innervation 9,13) .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…1 b, e, f). This pattern has also been reported in other studies 2,12,14) . Other authors, however, found no specific pattern of innervation 9,13) .…”
Section: Discussionsupporting
confidence: 91%
“…However, we found the mean VML fibre angle to be 5°, with a range between −10° to 12°, whereas numerous other authors have reported this angle to be 15-18° (e.g. 2,9,12,14) ). We found this to be almost exactly the angle of the VMO at the division between VMO and VML It is striking that what we found to be the fibre angle of the most proximal fibres of the VMO so closely resembles the mean VML fibre angle reported by some previous authors, and that the VMO/VML separation reported here is so much more proximal than expected.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations